Epidemiological study of overall survivability of individuals diagnosed with lung and bronchus cancer in Michigan between the years 1996 and 2017 - Georgette Nader; Akhil Sharma; Mahmoud Abdelsamia; Ling Wang; Lalitsiri Atti; Heather Laird‐Fick (Thoracic Cancer, 2024)
Abstract Introduction Lung and bronchus cancer is a leading cause of death in the United States. Compared with the national average, Michigan has an increased mortality rate and low early screening and treatment rates. This study aimed to explore the epidemiological trends and assess overall survival (OS) of patients diagnosed with lung cancer in Michigan from 1996 to 2017. Methods Data was acquired from the Michigan Cancer Surveillance Program (MCSP). Log‐rank test was used to test OS among the time periods, univariate and multivariate cox regression models were employed to determine factors that significantly affected OS. We hypothesized that the introduction of more inclusive lung cancer screening guidelines in 2013 would improve OS for patients diagnosed after its implementation and that individual characteristics and tumor characteristics would both affect OS. Results Notably, 153 742 individuals met inclusion criteria: 54.22% male and 45.78% female. Mean age at diagnosis was 69 years. No significant difference in OS was found among the three time periods (p = 0.99). Univariate analyses identified four individual characteristics associated with reduced OS: age at diagnosis, male sex, American Indian race, and living in rural or urban area. Reduced OS was associated with primary sites tumors at main bronchus, lung base, or within overlapping lobes, and SEER stage 7. Conclusions This study highlights several factors that influence OS. Consideration of these factors may be helpful as a community outreach tool to help increase early detection and reduce overall mortality.